Bird diversity in the coastal talukas of Sindhudurg District, Maharashtra, India - Golusu Babu Rao (Journal of Threatened Taxa, 2019)
The list of birds of Sindhudurg coastal district was compiled based on primary and secondary information.  All observations were made along the Sindhudurg coast, i.e., from Terekhol to Vijaydurg.  Wetland birds were recorded during sampling while terrestrial birds were recorded opportunistically.  Besides, we also collated bird occurrence records from published literature (including grey literature and online resources) to prepare a comprehensive list of birds for Sindhudurg coast.  During our study, we recorded 283 species, and 24 more species were compiled from secondary sources.  Altogether, 307 species belonging to 78 families and 22 orders were recorded from the Sindhudurg coast.  Order Passeriformes was dominant with 111 species.  Among the 307 species, four species are endemic to the Western Ghats.  Three species of vultures had been reported earlier but two were not encountered in recent years.  Great Knot (EN), Woolly-necked Stork (VU) and 14 other species (NT) fall under various threat categories of IUCN.  Species richness was higher in Vengurla (256) followed by Malvan (247) and Devgad talukas.  Construction of homestays, unregulated tourism in coastal areas, and conversion of natural habitats to meet increasing tourism are the major threats to the coastal avifauna of the district.  A high species richness of birds in Sindhudurg coast is attributed to the availability of a wide array of habitats (coastal to woodlands with different degrees of anthropogenic disturbances).  Considering the high species richness of birds and livelihood dependency of humans on the coastal zones, a few estuaries namely Mochemad, Karli and Mitbav estuaries may be recognized as community/ conservation reserve to manage the ecosystem sustainably for long-term conservation of these estuaries and sub-habitats therein.  Also, those sites can be perceived as Important Bird and Biodiversity Areas of IBCN as they fulfill the IBA criteria.